2004
DOI: 10.1038/ni1042
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of V(D)J recombination by a histone methyltransferase

Abstract: The tissue- and stage-specific assembly of antigen receptor genes by V(D)J recombination is regulated by changes in the chromatin accessibility of target gene segments. This dynamic remodeling process is coordinated by cis-acting promoters and enhancers, which function as accessibility control elements. The basic epigenetic mechanisms that activate or repress chromatin accessibility to V(D)J recombinase remain unclear. We now demonstrate that a histone methyltransferase overrides accessibility control element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 50 publications
2
70
0
Order By: Relevance
“…We have reported that a null G9a-mutation in embryonic stem (ES) cells led to a loss of H3-K9 dimethylation at the Mage-a promoter and reversed transcriptional repression of Mage-a genes (Tachibana et al 2002). Targeting of G9a and induction of H3-K9 methylation at antigen receptor gene segments suppressed their germline transcription and V(D)J recombination (Osipovich et al 2004). Furthermore, G9a-mediated H3-K9 methylation has been implicated in the silencing of developmentally regulated genes via interaction with CDP/cut (Nishio and Walsh 2004), the plasma cell transcription factor Blimp-1 (Gyory et al 2004), and the neuron-restrictive silencing factor NRSF/REST (Roopra et al 2004).…”
Section: ) G9amentioning
confidence: 99%
“…We have reported that a null G9a-mutation in embryonic stem (ES) cells led to a loss of H3-K9 dimethylation at the Mage-a promoter and reversed transcriptional repression of Mage-a genes (Tachibana et al 2002). Targeting of G9a and induction of H3-K9 methylation at antigen receptor gene segments suppressed their germline transcription and V(D)J recombination (Osipovich et al 2004). Furthermore, G9a-mediated H3-K9 methylation has been implicated in the silencing of developmentally regulated genes via interaction with CDP/cut (Nishio and Walsh 2004), the plasma cell transcription factor Blimp-1 (Gyory et al 2004), and the neuron-restrictive silencing factor NRSF/REST (Roopra et al 2004).…”
Section: ) G9amentioning
confidence: 99%
“…Apart from cis-elements in the immune receptor loci, including recombination signal sequence, enhancers and promoters [48,65], some trans-elements have been shown to play an important part in the regulation of V(D)J recombination [66][67][68]. Moreover, accumulating evidence has demonstrated the role of epigenetic factors in the regulation of V(D)J recombination, probably by altering the chromatin accessibility at the immune receptor loci [66,[69][70][71][72][73][74][75]. Future investigations into the upstream signals that regulate those known downstream regulators of V(D)J recombination should be able to provide insights into how the V(D)J recombination process can be manipulated.…”
Section: Future Challengesmentioning
confidence: 99%
“…Some combinations of Su(var) mutations increase meiotic recombination in Drosophila heterochromatin42, and loss of gene-silencing components in budding and fission yeasts increases both meiotic and somatic recombination in the rDNA33 ,43 . Similarly, the G9a H3K9 methyltransferase regulates accessibility of the V(D)J recombination machinery during mouse lymphocyte development 44 . Here, we expand on previous studies by demonstrating the impact of these mechanisms on nucleolar organization and the spatial arrangement of repeated sequences in the nucleus of a developing animal.…”
mentioning
confidence: 99%